Measuring Fiqih Learning Achievement of Junior High School Students Reviewed From Spiritual Intelligence - Agustin, Alvina; Kistoro, Hanif Cahyo Adi (At-tadzkir: Islamic Education Journal, 2024)
Spiritual intelligence is an essential manifestation in the success of Islamic religious education. Jurisprudence subjects are crucial subjects in Islamic religious education that discuss worship and muamalah material. This study aims to determine the relationship between students' spiritual intelligence and learning outcomes in the field of fiqh. This research is quantitative research with the type of survey research. The population of this research is all students of SMP Muhammadiyah 9 Yogyakarta, totalling 441 students. Based on the sampling technique using random sampling, a sample of 208 students was obtained from which data could be taken. The data collection technique used a questionnaire/questionnaire and student achievement results. After going through several data processing processes, many data are invalid and invalid, leaving 150 data analyzed. The data analysis technique used simple regression analysis with the help of the SPSS version 21 for the windows program. The results showed that spiritual intelligence had a positive and significant relationship with the fiqh learning achievement of SMP Muhammadiyah 9 Yogyakarta students, with a Pearson Correlation of 0.233. The significance value is the same, namely 0.004 <0.05, which means a positive correlation between the two variables. Although there is a positive relationship but based on the results of the decision seen from the guideline for the degree of correlation, 0.233 is in the order of 0.20 to 0.40, which means that there is a moderate correlation between spiritual intelligence and student fiqh learning achievement at SMP Muhammadiyah 9 Yogyakarta.